The space of capital: A latent class analysis of capital portfolios in Germany - Nora Waitkus; Olaf Groh-Samberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
The aim of this paper is to construct the "space of capital" based on disaggregated measures of capital portfolios and to analyze the dynamics of class mobility over time. Drawing on Pierre Bourdieu's concept of the "social space", we argue that it is possible to directly assess the structural dimensions of the social space as a space of (economic and cultural) capital, including wealth as an important but often neglected form of economic capital. Using household panel data from 2002-2012 (SOEP), we apply latent class analysis in order to detect distinct classes based on specific capital portfolios. We find nine classes with diverging capital portfolios. When interpreting the nine latent classes, we find clear evidence for the two main axis of the social space, namely the vertical axis of the overall volume of capital, and the horizontal axis representing the composition of capital in terms of the relative weight of economic and cultural capital. Further exploration of class mobility reveals that the horizontal axis is even more stable over time. Most mobility occurs along the vertical axis of the social space, while there is only little horizontal mobility indicating that individuals rarely change their investment and accumulation strategies. This research adds to Bourdieu inspired class analysis as well as sociological perspectives on wealth and accumulation.
Keywords: 330; social space; Bourdieu; capital; social class; wealth; mobility; latent class analysis